1985
DOI: 10.1093/nar/13.19.6999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HeLa cell DNA topoisomerase I by ATP and phosphate

Abstract: The relaxation activity of DNA topoisomerase I from HeLa cell nuclei is strongly inhibited by a variety of purine nucleotides in the presence but not absence of 1 mM potassium phosphate. For ATP, 3-4 nM causes nearly complete inhibition. The 2'-and 3'-AMP isomers are active as well in the presence of 1 mM phosphate, but the 5'-AMP isomer and adenosine are inert. At 3 nM ATP, the titration curve for phosphate is sigmoidal with inhibition beginning abruptly at about 0.5 nM. The negatively-supercoiled DNA isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…HeLa topo I and II were purified according to published procedures (13,14) except all columns were eluted with linear salt gradients. Topo I was inhibited by a factor of 50 under DNA unwinding assay conditions to be described, probably due to the inhibitory effects of ATP and creatine phosphate (15 …”
Section: Methodsmentioning
confidence: 87%
“…HeLa topo I and II were purified according to published procedures (13,14) except all columns were eluted with linear salt gradients. Topo I was inhibited by a factor of 50 under DNA unwinding assay conditions to be described, probably due to the inhibitory effects of ATP and creatine phosphate (15 …”
Section: Methodsmentioning
confidence: 87%
“…These conditions, however, can both inhibit DNA topoisomerase I and increase DNA topoisomerase II activity. Thus, ATP and phosphate inhibit topoisomerase I (Low and Holden, 1985;Castora and Kelly, 1986) whereas phosphorylation activates topoisomerase H (Sahyoun et al, 1986). Moreover, glycerophosphate is a phosphatase inhibitor (Foulkes and Rich Rosner, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that physiological concentrations of ATP (ϳ2 mM) can inhibit human Topo I (36). In another report, ATP was shown to inhibit human Topo I only in the presence of 1 mM KPO 4 (37). These conflicting reports prompted us to examine the effect of ATP and KPO 4 on the activity of HeLa Topo I in the presence or absence of 10 mM Mg 2ϩ (Table I).…”
Section: Expression and Purification Of Recombinant Forms Of Hu-mentioning
confidence: 99%